About a Large Botryoid Rhabdomyosarcoma in a Little Girl: Management Difficulties and Literature Review - Dehi Boston Mian; Vedi Andre Serges Loue; Sylvanus Koui (Case Reports in Obstetrics and Gynecology)
Background. Rhabdomyosarcoma (RMS) is a rare high-grade malignant tumor and the most common soft-tissue sarcoma, which occurs in young girl over 5 years old. Multimodality treatment associating with surgery, chemotherapy, and/or radiotherapy culminate in a >70% overall 5-year survival. This is the first case reported in 30 years of practice in Côte d’Ivoire, low- and middle-income country (LMIC). Objective. To summarize clinical data, the significant alternative chemotherapy efficiency and difficulties related to the prognosis evaluation in an LMIC. Case. A 2-year-old girl had been examined for a large mass in the vulvar region and clitoris. We carried out a biopsy for histopathologist exam. This allows pathologic, genetic, and biological characterization of nonmetastatic botryoid rhabdomyosarcoma. A multidisciplinary team decision of neoadjuvant chemotherapy was retained combining vincristine, cyclophosphamide, and actinomycin D or alternatively with Adriamycin. After 3 weeks of chemotherapy, significant volumetric reduction of tumor was observed. Yet a surgical removal was proposed but not performed because the patient has no longer consulted our medical center and was lost to follow-up. Therefore, we cannot assess the long-term evolution and prognosis. Conclusion. Embryonal RMS (ERMS) of clitoris is a rare malignant tumor of infant. Histology and immunohistochemistry are essential for diagnostic but unavailable in our context. We want to emphasize on the difficulties encountered in treatment and prognosis assessment. The primary free surgical removal of the vulva with adjuvant chemotherapy and/or radiotherapy must then be implemented in our practice.